Oświadczenie woli a skuteczna czynność prawna, glosa do uchwały SN z dnia 19 października 2018 r., III CZP 36/18 - Sokołowski, Tomasz (PRAWO i WIĘŹ, 2021)
The author discusses the consequences of the resolution of Supreme Court of October 19, 2018. The main question concerns the scope and prerequisites of the effective declaration of successor, made on future, accepting the succession estate, the declaration disclaiming the estate, or the consequences of remaining silent, i.e. inactivity (“silence”). The issue is related to the nature and structure of the acceptance of a succession estate as a unilateral legal act.